Utilization of Coconut Shells Activated Charcoal in Making Solid Soap from Used Cooking Oil - Amir Hamzah Siregar; Ardina Harahap (Talenta Publisher, 2023)
Research on the utilization of coconut shell activated charcoal in making solid soap from used cooking oil by adding variations in the concentration of coconut shell activated charcoal by 3%, 5%, 10% and without purification. So, several parameters can be determined to test the quality of used cooking oil, namely PV, free fatty acid (FFA), color, moisture content, and odor based on SNI 3741: 2013. The parameter value of used cooking oil without purification on PV is 15,1607 mekO2/ kg. FFA, which is 0.8244 mgKOH / g. Water content is 0.1321% b / b. Smell that is not normal. The resulting color is 10.28 red / 87.00 yellow. Value The parameters of the quality of cooking oil produced from the treatment process after the addition of a variation of coconut shell activated charcoal by 10% can reduce the PV of 5.5247 mecO2/kg. FFA which is 0.2817 mgKOH / g. Water content is 0.0798% b / b. The smell becomes normal. The resulting color is 3.40 red / 35.00 yellow. It can be concluded that the concentration of the addition of coconut shell activated charcoal, which is optimal in the processing process, is by adding coconut shell activated charcoal by 10% in used cooking oil to meet the cooking oil quality standards according to SNI 3741: 2013. Solid soap-free fatty acids were not detected in the study of making solid soap from purified cooking oil. The soap solution was pink when the testing process was titrated with KOH solution 0.1 N. This is presumably because the fatty acids in used cooking oil have reacted all with NaOH so that the free fatty acids cannot be measured.